2017
DOI: 10.1097/rct.0000000000000509
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Enhancement and Heterogeneity Are Associated With Treatment Response to Drug-Eluting Bead Chemoembolization for Hepatocellular Carcinoma

Abstract: Tumor heterogeneity and enhancement on arterial phase imaging may be predictive markers of treatment response to DEB-TACE among patients with HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…In the model, we employed an important factor, the homogeneous/heterogeneous vascularization of the tumor. Several lines of studies indicated the post-treatment lipiodol deposition and the response to TACE were correlated with tumor vascularization [32,33]. Besides, it has been reported that heterogeneous vascularization within the tumor is associated with poorly differentiated HCC cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…In the model, we employed an important factor, the homogeneous/heterogeneous vascularization of the tumor. Several lines of studies indicated the post-treatment lipiodol deposition and the response to TACE were correlated with tumor vascularization [32,33]. Besides, it has been reported that heterogeneous vascularization within the tumor is associated with poorly differentiated HCC cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…C-arm CT and volume perfusion CT (VPCT) for blood volume assessment have been reported by a prior study that they are able to predict the midterm tumor response of patients [ 21 ]. Furthermore, a study illustrates that tumor heterogeneity and tumor enhancement more than 50% are correlated with CR in HCC patients after DEB-TACE therapy [ 22 ]. And in the study of Kokabi N et al, they discover that the apparent diffusion coefficients (ADC) at baseline < 0.83 × 10 − 3 mm 2 /s is a predictive factor for both clinical response and survival of HCC patients after DEB-TACE [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“… 39 In addition, another retrospective cohort study of DEB-TACE disclosed that tumor heterogeneity and tumor enhancement >50% predicts better CR but with a limited sample size (only 32 patients). 40 Besides, a phase II trial illustrates that DEB-TACE achieves better objective response compared to cTACE in patients with HCC having Child-Pugh stage B, ECOG performance status 1, bilobar disease, or recurrent disease. 18 In our study, we observed baseline high AST, high CA199, portal vein invasion, higher Child-pugh stage, and higher BCLC stage were associated with less possibility of clinical response by DEB-TACE treatment, while high BUN predicted a better clinical response achievement.…”
Section: Discussionmentioning
confidence: 99%